The Hegemony of Heritage Ritual and the Record in Stone - L. Stein, Deborah (South Asia Across the Disciplines, 2018)
The Hegemony of Heritage makes an original and significant contribution to our understanding of how the relationship of architectural objects and societies to the built environment changes over time. Studying two surviving medieval monuments in southern Rajasthan-the Ambikā Temple in Jagat and the Śri Ékliṅgjī Temple Complex in Kailāshpurī-the author looks beyond their divergent sectarian affiliations and patronage structures to underscore many aspects of common practice. This book offers new and extremely valuable insights into these important monuments, illuminating the entangled politics of antiquity and revealing whether a monument's ritual record is affirmed as continuous and hence hoary or dismissed as discontinuous or reinvented through various strategies. The Hegemony of Heritage enriches theoretical constructs with ethnographic description and asks us to reexamine notions such as archive and text through the filter of sculpture and mantra.